Double-edged role of mechanical stimuli and underlying mechanisms in cartilage tissue engineering - Jia, Yao; Le, Hanxiang; Wang, Xianggang; Zhang, Jiaxin; Liu, Yan; Ding, Jiacheng; Zheng, Changjun; Chang, Fei (Frontiers in Bioengineering and Biotechnology, 2023)
Mechanical stimuli regulate the chondrogenic differentiation of mesenchymal stem cells (MSCs) and the homeostasis of chondrocytes, thus affecting implant success in cartilage tissue engineering. The mechanical microenvironment plays fundamental roles in the maturation and maintenance of natural articular cartilage, and the progression of osteoarthritis (OA). Hence, cartilage tissue engineering attempts to mimic this environment in vivo to obtain implants that enable a superior regeneration process. However, the specific type of mechanical loading, its optimal regime, and the underlying molecular mechanisms are still under investigation. First, this review delineates the composition and structure of articular cartilage, indicating that the morphology of chondrocytes and components of the extracellular matrix (ECM) differ from each other to resist forces in three top-to-bottom overlapping zones. Moreover, results from research experiments and clinical trials focusing on the effect of compression, fluid shear stress, hydrostatic pressure, and osmotic pressure are presented and critically evaluated. As a key direction, the latest advances in mechanisms involved in the transduction of external mechanical signals into biological signals are discussed. These mechanical signals are sensed by receptors in the cell membrane, such as primary cilia, integrins, and ion channels, which next activate downstream pathways. Finally, biomaterials with various modifications to mimic the mechanical properties of natural cartilage and the self-designed bioreactors for experiment in vitro are outlined. An improved understanding of biomechanically driven cartilage tissue engineering and the underlying mechanisms is expected to lead to efficient articular cartilage repair for cartilage degeneration and disease.